Pilot Competency and Capability Responsibilities, Strategy and Command - Green, Steven D. (Taylor & Francis, 2023)
Pilot Competency and Capability presents strategies for the air carrier pilot-in-command operating complex engineered systems within a complex natural environment. It bridges the gap between academic books and practical application by providing real-world examples of how various safety and operational theories work in practice.